Topical treatment with coenzyme Q10‐containing formulas improves skin's Q10 level and provides antioxidative effects. (9th December 2015) - Knott, Anja; Achterberg, Volker; Smuda, Christoph; Mielke, Heiko; Sperling, Gabi; Dunckelmann, Katja; Vogelsang, Alexandra; Krüger, Andrea; Schwengler, Helge; Behtash, Mojgan; Kristof, Sonja; Diekmann, Heike; et al.
Abstract: Ubiquinone (coenzyme Q10, Q10) represents an endogenously synthesized lipid‐soluble antioxidant which is crucial for cellular energy production but is diminished with age and under the influence of external stress factors in human skin. Here, it is shown that topical Q10 treatment is beneficial with regard to effective Q10 replenishment, augmentation of cellular energy metabolism, and antioxidant effects. Application of Q10‐containing formulas significantly increased the levels of this quinone on the skin surface. In the deeper layers of the epidermis the ubiquinone level was significantly augmented indicating effective supplementation. Concurrent elevation of ubiquinol levels suggested metabolic transformation of ubiquinone resulting from increased energy metabolism. Incubation of cultured human keratinocytes with Q10 concentrations equivalent to treated skin showed a significant augmentation of energy metabolism. Moreover, the results demonstrated that stressed skin benefits from the topical Q10 treatment by reduction of free radicals and an increase in antioxidant capacity. © 2015 BioFactors, 41(6):383–390, 2015